Diagnostic accuracy study of anorectal manometry for diagnosis of dyssynergic defecation. Issue 3 (12th March 2015) - Grossi, Ugo; Carrington, Emma V; Bharucha, Adil E; Horrocks, Emma J; Scott, S Mark; Knowles, Charles H
Abstract : Objective: The diagnostic accuracy of anorectal manometry (AM), which is necessary to diagnose functional defecatory disorders (FDD), is unknown. Using blinded analysis and standardised reporting of diagnostic accuracy, we evaluated whether AM could discriminate between asymptomatic controls and patients with functional constipation (FC). Design: Derived line plots of anorectal pressure profiles during simulated defecation were independently analysed in random order by three expert observers blinded to health status in 85 women with FC and 85 age-matched asymptomatic healthy volunteers (HV). Using accepted criteria, these pressure profiles were characterised as normal (ie, increased rectal pressure coordinated with anal relaxation) or types I–IV dyssynergia. Interobserver agreement and diagnostic accuracy were determined. Results: Blinded consensus-based assessment disclosed a normal pattern in 16/170 (9%) of all participants and only 11/85 (13%) HV. The combined frequency of dyssynergic patterns (I–IV) was very similar in FC (80/85 (94%)) and HV (74/85 (87%)). Type I dyssynergia ('paradoxical' contraction) was less prevalent in FC (17/85 (20%) than in HV (31/85 (36.5%), p=0.03). After statistical correction, only type IV dyssynergia was moderately useful for discriminating between FC (39/85 (46%)) and HV (17/85 (20%)) (p=0.001, positive predictive value=70.0%, positive likelihood ratio=2.3). Interobserver agreement was substantial or moderate for identifying a normal pattern, dyssynergia types I and IV, and FDD, and fair for types II and III. Conclusions: While the interpretation of AM patterns is reproducible, nearly 90% of HV have a pattern that is currently regarded as 'abnormal' by AM. Hence, AM is of limited utility for distinguishing between FC and HV.